2021
DOI: 10.1177/02537176211022146
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Psychiatric Morbidity in COVID-19-Positive Inpatients Referred to Consultation Liaison Psychiatry in a Tertiary Care Hospital

Abstract: Background: The COVID-19 pandemic has led to the risk of common mental illnesses. Consultation liaison psychiatry has been one of the most requested services in the face of this pandemic. We aimed to assess (a) the prevalence of psychiatric illness, (b) different types of psychiatric diagnoses, (c) presenting complaints, (d) reasons for psychiatric referrals, and (e) psychiatric intervention done on COVID-19 positive inpatients referred to consultation liaison psychiatry at tertiary care hospital. Method: This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 14 publications
1
1
0
Order By: Relevance
“…The results of our study showed a significant reduction in hospitalizations for surgical reasons, non-surgical ICUs, and infections (non-COVID), increasing those related to COVID. This unforeseen consequence of the switch in care focus impacted the LPTs, as is described in other published studies ( Butler et al, 2021 ; Prajapati et al, 2021 ). In our study, the proportion of requests for suicide risk assessment decreased during the pandemic period, related to confinement.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…The results of our study showed a significant reduction in hospitalizations for surgical reasons, non-surgical ICUs, and infections (non-COVID), increasing those related to COVID. This unforeseen consequence of the switch in care focus impacted the LPTs, as is described in other published studies ( Butler et al, 2021 ; Prajapati et al, 2021 ). In our study, the proportion of requests for suicide risk assessment decreased during the pandemic period, related to confinement.…”
Section: Discussionsupporting
confidence: 60%
“…On the other hand, there was an increase in the rate of a new diagnosis, the most frequent being adjustment disorders and delirium, both in a higher proportion than in previous months, especially in the case of delirium as reflected in the literature ( Rebora et al, 2021 ). There was also a significant decrease in bipolar disorder and neurocognitive disorder ( Butler et al., 2021 ; Prajapati et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%